Analisis Kekuatan Tarik Las Smaw Pada Pipa Carbon Steel A106 Grade B - Mahendra, Genta Arya Rahma; Ibad, Muhamad Nahrudin; Wulandari, Diah (CV. SINAR HOWUHOWU, 2026)
The purpose of this study is to analyze the welding strength, specifically the SMAW (Shielded Metal Arc Welding) method, on ASTM A106 grade B carbon steel pipes. These pipes are commonly used in the oil and gas industry, making it important to understand the mechanical properties that occur after the welding process. Tensile testing was conducted on specimens taken from welded pipe joints, using SMAW as the welding method parameter. The results of the test indicate that the welding method significantly influences tensile strength, elongation, and other mechanical properties. This study found that maximum strength is achieved at certain parameters, highlighting the importance of control in the welding process to ensure joint quality. In addition, microscopic analysis of the microstructure shows that the composition and phase characteristics of the weld affect joint strength. The findings of this research are expected to provide guidance for industry in improving welding quality and the durability of carbon steel pipe joints, as well as serve as a reference for further studies in developing more efficient and effective welding techniques.